A decline in HIV and syphilis epidemics in Chinese female sex workers (2000-2011): a systematic review and meta-analysis. - Zongxing Yang; Junwei Su; Xiaorong Peng; Nanping Wu (PLoS ONE, 2013)
Background Female sex workers (FSWs) play an important role in transmitting HIV and syphilis from high-risk groups to the general population. However, the trends in HIV and syphilis epidemics in Chinese FSWs in the period after 2000 are unclear to date. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement was followed. Seven databases were searched for published peer-reviewed articles. The incidence of HIV and syphilis in FSWs in different time periods, provinces and workplaces in China were separately pooled by meta-analysis. Correlation analysis was conducted between HIV and syphilis incidence and study time, respectively. Results After 1,662 articles were screened, 190 published papers were included in the final analysis. Estimated HIV prevalence was 0.284% (95% CI: 0.080-0.488%) in the period 2000-2002, 0.211% (95% CI: 0.149-0.273%) in 2003-2005, 0.242% (95% CI: 0.190-0.294%) in 2006-2008 and 0.041% (95% CI: 0.024-0.058%) in 2009-2011. The corresponding syphilis prevalence was 9.669% (95% CI: 7.810-11.529%), 4.970% (95% CI: 4.384-5.556%), 4.404% (95% CI: 4.032-4.775%) and 3.169% (95% CI: 2.738-3.600%), respectively. Spearman rank correlation coefficients were -0.165 (p = 0.002) between HIV prevalence and study time, and -0.209 (p = 0.000) between syphilis prevalence and study time. The combined HIV prevalence was 0.318% (95% CI: 0.156-0.479%) in medium and high-tier workplaces and 0.393% (95% CI: 0.176-0.610%) in low-tier workplaces. The corresponding syphilis prevalence was 3.216% (95% CI: 2.192-4.240%) and 13.817% (95% CI: 10.589-17.044%), respectively. Conclusions Our data suggested a decline in HIV and syphilis epidemics in FSWs in China on a national level during the study period (2000-2011). FSWs in low-tier workplaces should be given more attention in the future to ensure they are included in prevention programs for HIV and sexually transmitted diseases.